Fijian adolescents' understanding and evaluation of climate change: Implications for enabling effective future adaptation. (6th April 2018) - Scott‐Parker, Bridie; Kumar, Roselyn
Abstract : Pacific Island countries are particularly vulnerable to future manifestations of climate change due to high coastline‐to‐land‐area ratios, and high dependence of inhabitants on natural ecosystems. While everyone in the Pacific Islands should participate in climate change adaptation activities, it is the young people, given they are the generation likely to not only bear the burden of climate change, but to lead and live effective climate change adaptation activities and strategies specific to their region, the involvement of youth is critical. Pacific Island youths are often marginalised within traditional decision‐making hierarchies, therefore they are typically excluded from participating in meaningful discussions at community and government levels. Discussions were held with 30 adolescents aged 14–18 years in Fiji to explore knowledge and experiences regarding climate change. Participants revealed their dismay at their inability to talk to family – who they consider are not doing enough – about what they consider as appropriate responses to climate change, recommending the help of an authoritative outsider who could speak to their community leaders and family. Discussions also revealed that Fijian youth could not distinguish between changes in the climate and normal weather events, attesting to the importance of climate‐change education and awareness‐raising efforts within the Pacific Islands more generally.